Temporary Contemporary Creating vibrant spaces to support the conditions for creative and cultural activity - Bailey, Rowan; Clear, Nic; Cotton, Chris; Davies, Kath; Fitzpatrick, Donal; Powell, Anna; Pittwood, Linda Jean (University of Huddersfield Press, 2020)
This is the first book that documents and reflects on an aspect of the Temporary Contemporary initiative. Launching in 2018, Temporary Contemporary is a collaboration between the School of Art, Design and Architecture at the University of Huddersfield and Kirklees Council. This collaboration, in the form of an action research project, has sought to reflect on the efficacy, meanings and wider contribution of cultural activity in Huddersfield town and beyond. It is one small part of a bigger project about the future cultural heart of Huddersfield. The title Creating Vibrant Spaces to Support the Conditions for Creative and Cultural Activity refers to the aims of Temporary Contemporary in its entirety. The initiative achieves these aims through populating former retail spaces in the town with exhibitions and events, fostering partnerships and creating networking opportunities for cultural and creative producers, repurposing fine historic buildings and making connections with rich cultural traditions in the town including music, theatre and textiles. This book provides one contribution to the many discussions about the role of culture in towns and cities. The insights of our collaborative research may be of interest and use to policy makers, academics, artists, curators and anyone else with a concern about the cultural and social future of towns and cities in the UK and beyond.